Skin: A mirror of internal malignancy - Rita V Vora; RahulKrishna S Kota; Nilofar G Diwan; Nidhi B Jivani; Shailee S Gandhi (Indian Journal of Medical and Paediatric Oncology)
Skin manifestations are a reflection of many of the internal diseases. Sometimes, skin disease may be the only manifestation of the internal disease. Internal malignancies may give rise to a number of cutaneous manifestations through their immunological, metabolic, and metastatic consequences. Curth proposed criteria to establish a causal relationship between a dermatosis and a malignant internal disease. Malignancy can present with a plethora of cutaneous manifestations. Here, we describe in brief about various skin manifestations of internal malignancies.